Verbal accompaniment, following and pairing - Mahmoud, Shaima Mohamed; AlAni, Lama Faeq Jamil (Al-Adab Journal, 2023)
The research sought to study one of the phenomena of Arabic that the scholars had been concerned with and presented their works to, as they tried to draw an image of it, to this end, we have taken several avenues, represented by extrapolating everything that is related to following and pairing up, as this phenomenon is based on a system of rulings that produce many linguistic images that the Arab was afraid of in his words; In fulfillment of the speech systems and context, even if it contradicts the origin of the linguistic situation. This study was based on the descriptive approach in research and analysis, and it tended to note the phenomenon in its various forms, in the Iraqi feminist novel, then monitor and define it, and we presented the opinions of scholars in determining it, and we concluded from all that to clarify the precise concept of it, and we referred to the verbal accompaniments that represent this phenomenon. We hope with this humble research that we have contributed to the service of the Arabic language, and we ask God for success after that.